2019
DOI: 10.1371/journal.pone.0212654
|View full text |Cite
|
Sign up to set email alerts
|

Optimal iron concentrations for growth-associated polyhydroxyalkanoate biosynthesis in the marine photosynthetic purple bacterium Rhodovulum sulfidophilum under photoheterotrophic condition

Abstract: Polyhydroxyalkanoates (PHAs) are a group of natural biopolyesters that resemble petroleum-derived plastics in terms of physical properties but are less harmful biologically to the environment and humans. Most of the current PHA producers are heterotrophs, which require expensive feeding materials and thus contribute to the high price of PHAs. Marine photosynthetic bacteria are promising alternative microbial cell factories for cost-effective, carbon neutral and sustainable production of PHAs. In this study, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…Marine purple sulfur bacteria are categorized to the first group, whereas purple non-sulfur bacteria belong to the second group. We also found that iron concentrations (ferric citrate) affect the cell growth and PHA production in R. sulfidophilum (Foong et al, 2019). Very low concentrations of iron (1–2 μM) was sufficient to promote cell growth and a high PHA yield (1,000 mg/L) during the logarithmic phase.…”
Section: Pha Productionmentioning
confidence: 76%
“…Marine purple sulfur bacteria are categorized to the first group, whereas purple non-sulfur bacteria belong to the second group. We also found that iron concentrations (ferric citrate) affect the cell growth and PHA production in R. sulfidophilum (Foong et al, 2019). Very low concentrations of iron (1–2 μM) was sufficient to promote cell growth and a high PHA yield (1,000 mg/L) during the logarithmic phase.…”
Section: Pha Productionmentioning
confidence: 76%
“…Rhodovulum and particularly Paracoccus are Rhodobacteraceae with potential beneficial roles for C. lentillifera. Rhodovulum species have a high metabolic versatility with the capability to degrade organic pollutants, to produce polymers and to contribute with photosynthetic functions (Khandavalli et al ., 2018; Foong et al ., 2019; Baker et al ., 2021). Paracoccus is a common genus among seaweed-associated bacteria with a key role in the cycle of nitrogen and in the production of siderophores (Mei et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, during log phase the expression of phaC1 transcript and phaZ increased which consequently led to a decrease in PHA accumulation. Marine PNSB Rhodovulum sulfidophilum [ 147 ] Nutrient Syngas devoid of carbon monoxide and phosphorous, in fed- batch cultivation with controlled acetate input 30 % w/w PHB produced. CO was converted to carbon dioxide via the action of CO dehydrogenase.…”
Section: Resource Recovery Applications Of Anoxygenic Phototrophic Bamentioning
confidence: 99%